Triangeliphthalides A–D: bioactive phthalide trimers with new skeletons from Angelica sinensis and their production mechanism. Issue 44 (13th May 2019) - Zou, Jian; Chen, Guo-Dong; Zhao, Huan; Wang, Xiao-Xia; Zhang, Zai-Jun; Qu, Yi-Bo; He, Rong-Rong; So, Kwok-Fai; Yao, Xin-Sheng; Gao, Hao
Abstract : Four bioactive phthalide trimers with new skeletons were isolated from Angelica sinensis, and their production mechanism was proposed. Abstract : Triangeliphthalides A–D (1–4 ), four novel phthalide trimers with two new linkage styles, were isolated from Angelica sinensis, together with two related phthalide dimers (5–6 ). Their structures including absolute configurations were determined. The production mechanism of phthalide polymers was proposed, and their bioactivities were also evaluated.